2020
DOI: 10.1021/acsami.0c19634
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electrified Liquid–Solid Interfaces with Scanning Electron Microscopy

Abstract: Electrical double layers play a key role in a variety of electrochemical systems. The mean free path of secondary electrons in aqueous solutions is on the order of a nanometer, making them suitable for probing of ultrathin electrical double layers at solid-liquid electrolyte interfaces. Employing 2 graphene as an electron-transparent electrode in a two-electrode electrochemical system, we show that the secondary electron yield of the graphene-liquid interface depends on the ionic strength and concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The basic understanding is that the physicochemical processes within the 1 −100 nm thin layer at the solid/liquid interfaces play the most important role in controlling the performance of such devices. The structure and dynamics of the electrified interfaces have been debated for more than one and a half centuries and revisited recently in theoretical work by Bazant and Kornyshev. Over the last three decades, significant experimental and theoretical efforts have been devoted to understanding the composition and structure and the numerous other properties of these ultranarrow interfaces. In these efforts, in addition to the well-established electrochemical metrology, advanced optical, microscopy, and scattering techniques have been utilized. These have revealed that the screening dynamics evolving on multiple time and length scales are due to various diffusion and relaxation processes. This has been also corroborated by simulations. , These studies have revealed that the polarization of ILs includes medium–slow (0.1 s–10 s) and ultraslow (10 2 –10 4 s) evolutions, in addition to the fast electrical double-layer (EDL) formation (1–10 ns), which also proceeds on short (1–10 nm), medium (<1 μm), and long (>100 μm) length scales. Therefore, for extended IL devices, the information reflecting not only the solid/liquid interface but also the bulk liquid and electrodes must be accounted for comprehensive analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic understanding is that the physicochemical processes within the 1 −100 nm thin layer at the solid/liquid interfaces play the most important role in controlling the performance of such devices. The structure and dynamics of the electrified interfaces have been debated for more than one and a half centuries and revisited recently in theoretical work by Bazant and Kornyshev. Over the last three decades, significant experimental and theoretical efforts have been devoted to understanding the composition and structure and the numerous other properties of these ultranarrow interfaces. In these efforts, in addition to the well-established electrochemical metrology, advanced optical, microscopy, and scattering techniques have been utilized. These have revealed that the screening dynamics evolving on multiple time and length scales are due to various diffusion and relaxation processes. This has been also corroborated by simulations. , These studies have revealed that the polarization of ILs includes medium–slow (0.1 s–10 s) and ultraslow (10 2 –10 4 s) evolutions, in addition to the fast electrical double-layer (EDL) formation (1–10 ns), which also proceeds on short (1–10 nm), medium (<1 μm), and long (>100 μm) length scales. Therefore, for extended IL devices, the information reflecting not only the solid/liquid interface but also the bulk liquid and electrodes must be accounted for comprehensive analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In SEM, the surface potential variations are observed as a reduction/enhancement of the secondary electron (SE) intensity, while in XPS, the potential-induced variations in the measured photoelectron kinetic energy manifest as binding energy (BE) shifts of all peaks. The ability of SEM to probe the potential distribution across the surface is routinely used to study the doping profiles, , p–n and Schottky barriers in semiconductors, for complementary metal–oxide–semiconductor device diagnostics, intercalation and formation of solid/electrolyte interface layers, electromigration in electrochemical devices, and more recently in liquid electrolytes . Electrical potential distribution/variations in solid/liquid electrolyte interfaces, as revealed by XPS, are even more informative since the sign, the magnitude, and also the variations in cation/anion ratios are directly quantifiable. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the molecular details of electrolytes at the solid/liquid (mostly aqueous) interface have been explored by many sophisticated techniques: ultrafast time-resolved second harmonic generation (SHG), sum-frequency generation (SFG), X-ray absorption spectroscopy in the electron yield mode (XAS), , surface enhanced Raman spectroscopy (SERS), infrared nanospectroscopy (nano-FTIR), , small-angle X-ray scattering (SAXS), scanning electron microscopy, , ambient pressure and standing wave X-ray photoelectron spectroscopy (APXPS), and electrochemical surface force measurements. , The measurements with appreciable sensitivity to signals from interfacial regions , provide characteristic times of solvation dynamics and mechanisms of cation adsorption as well as molecular scale details on interfacial ion concentration, local pH, the effects of the electrode bias on the structure of the solvent, and the potential drop in the immediate vicinity of an electrode.…”
mentioning
confidence: 99%